2018
DOI: 10.1523/eneuro.0346-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Common Sense in Choice: The Effect of Sensory Modality on Neural Value Representations

Abstract: Although it is well established that the ventromedial prefrontal cortex (vmPFC) represents value using a common currency across categories of rewards, it is unknown whether the vmPFC represents value irrespective of the sensory modality in which alternatives are presented. In the current study, male and female human subjects completed a decision-making task while their neural activity was recorded using functional magnetic resonance imaging. On each trial, subjects chose between a safe alternative and a lotter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Other possible parameters such as valence and arousal (Russell, 1980), value (Levy & Glimcher, 2012; Shuster & Levy, 2018), Fourier features (Sievers et al, 2019), HMAX (Riesenhuber & Poggio, 1999), and motion energy (Nishimoto et al, 2011) certainly covary with the stimulus feature and emotion judgment predictors. Because these and similar measures would be fully dependent on the model parameters, including them as controls would introduce collinearity and create post-treatment bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible parameters such as valence and arousal (Russell, 1980), value (Levy & Glimcher, 2012; Shuster & Levy, 2018), Fourier features (Sievers et al, 2019), HMAX (Riesenhuber & Poggio, 1999), and motion energy (Nishimoto et al, 2011) certainly covary with the stimulus feature and emotion judgment predictors. Because these and similar measures would be fully dependent on the model parameters, including them as controls would introduce collinearity and create post-treatment bias.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Russell's (1980) circumplex model organizes emotions in terms of their valence (positive-negative) and degree of arousal. These and other possible parameters, such as warmth and dominance (Kiesler, 1983) or value (Levy & Glimcher, 2012;Shuster & Levy, 2018) certainly covary with the stimulus features and emotion judgments used in the model described above.…”
Section: Limitations and Future Directions: Toward Comprehensive Expementioning
confidence: 95%
“…In perception this is known as the Weber-Fechner function [ 18 ], which states that the increase in the perceived magnitude of a certain stimulus declines as the stimulus intensity increases, and in value-based choice it is known as the Bernoulli function, or the utility function [ 19 ], which describes the notion that the marginal utility of a certain object declines as the total amount of this object increases. Second, value modulation was observed in both visual cortex [ 20 ] and auditory cortex [ 21 ] in a modality-specific way [ 22 ]. Moreover, recent studies have shown that visual selective attention is also driven by the learned value of a stimulus [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…On this account, sensory regions represent conjunctions of task-relevant environmental features, such as those associated with emotion expressions, supporting direct perception of social information. 20,37 Other possible parameters, such as valence and arousal, 38 value, 39,40 Fourier features, 15 HMAX, 41 and motion energy, 42 certainly covary with the stimulus feature and emotion judgment predictors. Because these and similar measures would be fully dependent on the model parameters, including them as controls would introduce collinearity and create post-treatment bias.…”
Section: Articlementioning
confidence: 99%